THE EFFECT OF DIFFERENT KOH CONCENTRATIONS ON THE VALUE OF THE DEACETYLATION DEGREE OF CHITOSAN FROM PENSI SHELLS (Corbicula moltkiana) - Angki Angelo Delevio; Mery Sukmiwati; Edison Edison (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
Abstract               This study aimed to determine the effect of different KOH concentrations on the value of the deacetylation degree of chitosan from pensi shells (Corbicula moltkiana). The treatments given were differences in the KOH concentration of 40, 50 and 60%. The analysis parameters observed were the proximate test and FTIR. The results based on the standard of ash content, moisture content and degree of deacetylation showed that 60% KOH concentration was the best with the lowest water and ash content and the highest deacetylation degree. namely the water content of 1.46%, the ash content of 9.42 and the degree of deacetylation of 53.58%.Keywords Chitin, Chitosan, Corbicula moltkiana, KOH and  Pensi shells.